Pengaruh Penggunaan Lembar Kegiatan Peserta Didik Berbasis Model APOS Berbantuan Geogebra Terhadap Keterampilan Berpikir Kritis Matematika - Istikomar Istikomar; Hanifah Hanifah; Hari Sumardi (Universitas Veteran Bangun Nusantara, 2022)
The purpose of this research is to determine the effect of using student activity sheets based on the Geogebra-assisted APOS model on mathematical critical thinking skills in quadrilateral material in class VII SMP Negeri 1 Bengkulu Selatan. The research design used is a quasi-experimental design with a population of all seventh-grade students at SMP Negeri 1 Bengkulu Selatan. The sample technique research used is a random sampling technique, to obtain a sample group in the activity of 2 classes, namely the experimental class and the control class. This study uses an instrument in the form of a pretest and a posttest in the form of an essay that has been tested. After doing the research, the average obtained from the post-test results for the experimental class was 82.17 and the average post-test results for the control class was 70.74. These results were obtained from the results of hypothesis testing with the ANCOVA test using SPSS21 software with = 0.05. From this test, sig(0.000) < 0.05 was obtained so that there was a significant effect of using the APOS model-based student activity sheet which was assisted by Geogebra on the ability to think critically in mathematics.